Kingdom Come : Revisioning Pentecostal Eschatology - Thompson, Matthew K. (Journal of Pentecostal Theology Supplement Series, 2010)
In his Pentecostal Spirituality: A Passion for the Kingdom (1993), theologian Steven J. Land issued a clarion call for Pentecostal theologians to reconsider eschatology outside the categories of premillennial dispensationalism. Kingdom Come: Revisioning Pentecostal Eschatology is Matthew Thompson's constructive answer to Land's invitation. Thompson persuasively argues that Pentecostalism's adoption of premillennial dispensationalism as a hermeneutic, as a philosophy of history and as an eschatology robs the movement of the potential for dynamic growth and of profound experiences of the power of the Holy Spirit. Thompson concludes his account with an engagement of the eschatologies of John Fletcher, Jürgen Moltmann and Sergius Bulgakov in order to construct what he terms a genuinely Pentecostal eschatology formulated thematically through the lens of the five-fold Pentecostal Full Gospel.